Linguoculturological Characteristics of Economic Discourse About the Family in Russian, Vietnamese and Danish Media - Vera V. Boguslavskaya; Khuong Thi Thu Trang; Albertina G. Ratnikova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The study and interpretation of the media discourse devoted to the family as a universal human value are urgent tasks of modern linguistics. The object of the research presented in the article is the economic discourse about the family of modern Russian, Vietnamese and Danish popular social-and-political national publications, and the purpose is to describe the linguistic and cultural characteristics of this discourse by identifying its value – semantic content expressed in the peculiarities of the actualization of the image of the family. Using the methods of content analysis, comparison of dictionary definitions of the words semya, gia dinh, familie and their distributive analysis, the features of the image of the family in the economic discourse of Russian and foreign media were found. In the Russian media, the image of a family is actualized by lexical means, which indicate the presence of children in it, its need for material support and social protection, the need to protect traditional family values, units that actualize the image of a large family. In the Vietnamese media, the image of the family is formed by lexical means, which characterize the problems of financial distress of families, determining the family’s belonging to the working class, actualizing the importance of family support by its members and their responsibility for its well-being. In the Danish media, the image of the family is formed by lexical means, which indicate the presence of a family business, characterizing the financial well-being of families, actualizing the image of the royal family.